PENCEGAHAN STUNTING DENGAN PENERAPAN PHBS DAN PENGGUNAAN SENYAWA ALAMI : PENCEGAHAN STUNTING DENGAN PENERAPAN PHBS DAN PENGGUNAAN SENYAWA ALAMI (Jurnal Mitra Masyarakat (JMM), 2022)
Stunting is a chronic malnutrition problemcaused by a lack of nutritional intake for a long time and not caused by hormonal disorders or diseases. Malnutrition in children can cause children to become sick easily, not optimal body postures, intelligence below normal and increase mortility in infants and children. Stunting can result in long-term economic losses for Indonesia. The purpose of this activity is to provide insight to the community to prevent stunting to thrive in children. This activity is carried out online with the target audience of the general public participating in the webinar. To determine of participants education, an evaluation was conducted using pre test and post test questionnaires to participants, then analyzed descriptively. The result of this activity is that the level of community knowledge based on results of the pre test and post test has increased significantly, which is almost 86,42%. This can be seen from the discussion and questions given to the speakers and the highest score obtained. The highest score after the pre test was obtained up to 100 points while the lowest was 15 points. The highest score after the post test is obtained up to 100 points while the lowest is 30 points.